Latency, flashback and resilience in Amit Majmudar’s Partitions and Jennifer Bradbury's A Moment Comes - Kramutally, Hasnaa (2017)
Unlike many studies which have focussed mostly on the political controversies and the violence against women during Partition, my study examines the concepts of latency, flashback and resilience as a response to the experience of rape, molestation and societal violence through the female characters in the selected novels. This study aims to examine the psychological reactions of Simran Kaur from Partitions (2011) by Amit Majmudar (b. 1979) and Anupreet from A Moment Comes (2013) by Jennifer Bradbury (b. 1970) to the experience of rape and molestation through latency and flashback and how they cope with the effects of societal violence due to their gender as female and faith as Sikh through resilience. Both texts are analyzed based on the textual analysis method focussing on rape, molestation, and societal violence during Partition as depicted by the authors. By applying concepts from the Trauma Theory, this study employs the conceptual frameworks of latency and flashback by Cathy Caruth (1995) and the conceptual framework of resilience by George A. Bonnano (2005). This study reveals the response of Simran Kaur and Anupreet to the experience of rape, molestation, and societal violence, which have been depicted in assorted forms in both novels, through latency, flashback, and resilience. In Partitions, Simran Kaur experiences latency while being molested and raped by Ayub and Saif, and the traumatic experience returns through flashback when she hears the sound of a truck. In addition, she demonstrates resilience when she volunteered as a nurse in a Sikh refugee camp in Amritsar. Besides, in A Moment Comes, Anupreet experiences latency while being molested, scarred on her face and threatened with rape by two male Muslim fanatics on two different occasions and the traumatic experience returns to her through repetitive thoughts at night. In contrast, she demonstrates resilience when she helped a Muslim boy escape the violence of Punjab in a crate to Bombay. Findings from this study can contribute to future research through a combination of the conceptual frameworks of latency, flashback, and resilience by Caruth and Bonanno by examining how the male characters in Partitions and A Moment Comes respond to the traumatic experience of Partition and the effects of communal violence. Also, the combined conceptual frameworks can be further broadened to include the concept of space in ecocriticsm where future research can be conducted to examine how the author’s depiction of inner or outer space either impede or alleviate a character’s latency, flashback or resilience in coping with their traumatic experiences.